Population structure of Phytophthora infestans collected from potatoes in Ecuador, Colombia, Peru, Bolivia and Uruguay - Izarra, M.; Coca-Morante, M.; Pérez, W.; Sánchez, L.; Gamboa, S.; Valle, D.; Cuarán, V.; Guerra-Sierra, B.; Kreuze, Jan F. (2026)
Late blight, a destructive disease affecting potatoes, is caused by the oomycete Phytophthora infestans and remains a critical threat worldwide. The potential for sexual reproduction in production areas near the Peru–Bolivia border remains high due to the historical presence of mating type A2 in Bolivia and the current presence of mating type A1 in Peru. In Ecuador, there has been a past coexistence of A1 (P. infestans) and A2 (P. andina), while in Colombia, P. infestans has mainly exhibited mating type A1. These neighboring countries were compared with strains from Uruguay, which historically had A2 but now shows A1. We examined the genetic structure of South American P. infestans populations using 182 isolates: 97 from Bolivia and southern Peru, 14 from Colombia, 57 from Ecuador (1993–2022), and 14 from Uruguay. The isolates were characterized by clonal lineage, mitochondrial haplotype, and mating type. In Bolivia, only the lineage/haplotype 2A1/Ia was identified, whereas Peru exhibited both 2A1/Ia and EC1/IIa, all of which were mating type A1. Puno was the sole department where both lineages were present. In older Ecuadorian populations, we found US1/Ib and EC1/IIa (P. infestans), as well as EC2/Ic and EC3/Ia (P. andina), while recent populations showed only US1. In Colombia, EC1/IIa and a new lineage, CO4 (Ia), were discovered. In Uruguay, 2A1/Ia was predominant. These results offer updated insights into the genetic diversity and geographic distribution of P. infestans across South America and aid in the development of enhanced late blight management strategies.